Pengaruh Pengetahuan Investasi, Tingkat Financial Literacy dan Faktor Umur Terhadap Keputusan Investasi Emas Pada Pegadaian SoE - Paulina Digta Isu; Fransina W. Ballo; Maria P. L. Muga; Sarlin P. Nawa Pau (BAJ: Behavioral Accounting Journal, 2022)
This study aims to determine the effect of investment knowledge, level of financial literacy and age factors on individual investment decisions at PT. Pegadaian (Persero) SoE Branch. The Data used in this study were obtained using questionnaires. This study uses a quantitative research approach. The population and sample studied in this study are customers of PT. Pegadaian (Persero) SoE Branch. The sampling method in this study is simple random sampling using Slovin formula that produces 100 respondents. The method used is descriptive statistical analysis technique and using validity testing technique, reliability test, classical assumption test, multiple linear regression and hypothesis test with thehelp of SPSS 25 application. Data collection techniques used using questionnaires, observation and documentation. The results of this study stated that the variables of investment knowledge and the level of financial literacy partially significant effect on individual investment decisions while the variable age factor partially does not affect individual investment decisions.Variables of investment knowledge, level of financial literacy and age factors simultaneously affect individual investment decisions